Luminescent Properties and Cytotoxic Activity of 2-phenylbenzoxazole Fluorosulfate Derivatives; International Journal of Molecular Sciences; Vol. 26, iss. 15 - Danilenko N. V. Nadezhda Viktorovna; Lutsuk M. O. Mariya Olegovna; Ryadun A. A. Alexey Andreevich; Pavlov D. I. Dmitry Igorevich; Plotnikov E. V. Evgeny Vladimirovich; Eskova D. D. Darjya Dmitrievna; Klimenko Yu. D. Yuliya Dmitrievna; Potapov A. S. Andrey Sergeevich; Khlebnikov A. I. Andrey Ivanovich (2025, 2025)
Title screen